Metabolomics assessment reveals oxidative stress and altered energy production in the heart after ischemic acute kidney injury in mice - Fox, Benjamin M; Gil, Hyo-Wook; Kirkbride-Romeo, Lara; Bagchi, Rushita A; Wennersten, Sara A; Haefner, Korey R; Skrypnyk, Nataliya I; Brown, Carolyn N; Soranno, Danielle E; Gist, Katja M; Griffin, Benjamin R; Jovanovich, Anna; et al. (Kidney international, 2019)
Acute kidney injury (AKI) is a systemic disease associated with widespread effects on distant organs, including the heart. Normal cardiac function is dependent on constant ATP generation, and the preferred method of energy production is via oxidative phosphorylation. Following direct ischemic cardiac injury, the cardiac metabolome is characterized by inadequate oxidative phosphorylation, increased oxidative stress, and increased alternate energy utilization. We assessed the impact of ischemic AKI on the metabolomics profile in the heart. Ischemic AKI was induced by 22 minutes of renal pedicle clamping, and 124 metabolites were measured in the heart at 4 hours, 24 hours, and 7 days post-procedure. Forty-one percent of measured metabolites were affected, with the most prominent changes observed 24 hours post-AKI. The post-AKI cardiac metabolome was characterized by amino acid depletion, increased oxidative stress, and evidence of alternative energy production, including a shift to anaerobic forms of energy production. These metabolomic effects were associated with significant cardiac ATP depletion and with echocardiographic evidence of diastolic dysfunction. In the kidney, metabolomics analysis revealed shifts suggestive of energy depletion and oxidative stress, which were reflected systemically in the plasma. This is the first study to examine the cardiac metabolome after AKI, and demonstrates that effects of ischemic AKI on the heart are akin to the effects of direct ischemic cardiac injury.